The present status of pepper in Malaysia - Bong, Joseph Choon Fah; Saad, M. S. (1985)
Pepper has been cultivated in Malaysia for more than 100 years. It is one of the most important agricultural crop of Sarawak. As more than 95 % of the.crop is grown in Sarawak. this paper will emphasize on the pepper situation in Sarawak. The production of pepper in Sarawak has declined by some 540/0 since 1979. The estimated area under pepper cultivation at present was between 5000 - 6000 ha. Factors contributing to the decline in the pepper production were discussed in the context of present situation. The impact of cocoa as an alternative to pepper was highlighted. The status of pepper research in the country was also discussed.